Carer experience of back pain is associated with adolescent back pain experience even when controlling for other carer and family factors - O'Sullivan, Peter; Straker, Leon; Smith, Anne; Perry, Mark; Kendall, Garth (Lippincott Williams and Wilkins, 2008)
Objectives: The study objectives were (1) to determine if adolescent back pain is related to carer back pain; and (2) to examine whether other carer and family factors accounted for any such relationship. Methods: Back pain experience was collected independently from 1608 fourteen-year-old adolescents and their care givers by questionnaire. Measures of back pain impact on carers were also collected (modified activities, missed work, sought professional help, took medication). Other carer factors examined were age, sex, smoking habits, depression, anxiety, and stress. Familial factors examined included income, stressful events, and family functioning. Odds ratios were calculated to describe familial associations with multivariate modeling used to examine the influence of other carer and family factors. Results: Lifetime prevalence of back pain was 46.5% for adolescents and 72% for their carers. Having a carer with backpain increased the risk of back pain for adolescents, and this was magnified if both carers had back pain (odds ratio 1.61). Adolescent back pain was not associated with primary carer age, sex, depression, anxiety, or stress but was related to family stressful events. However, these other factors did not diminish the association between carer back pain and adolescent backpain. Discussion: Carer experience of back pain is clearly associated with adolescent experience of back pain. Although other carer and family factors are also associated, the carer's back pain experience is not a surrogate measure of these other factors suggesting other genetic and behavioral mechanisms may be important for adolescent back pain development.